1 Cardiovascular Diseases Risk Assessment at Menopause - Sudhaa Sharma; Vishal R. Tandon; Annil Mahajan (Dr. Annil Mahajan, 2022)
The risk of cardiovascular disease increases during menopause due to oestrogen deficiency. Women both from urban or rural area have the enhanced risk in similar manner. Further, the cardiovascular disease related mortality remains the main killer disease in women more than men after menopause